Plan de mejoramiento de la empresa Distriolmedo CÍA. LTDA. de la ciudad de Latacunga - Olmedo Andino, Nycol Thalia (2015)
The improvement plan for the company Distriolmedo Cía. LTDA. aims to perfect the work system in its daily operations. It is important to emphasize that each area of the company was taken into consideration in order to carry out adequate planning given that the following will be effected and optimized: Efficient and timely solutions for the problems or complaints presented daily. Fulfillment of all safety and security standards. Staff training in order to create a favorable working environment. Meeting of standards with trucks during the transport of the product and return to the depot. Video monitoring of the truck routes for safety with a camera installed in each vehicle. Building of a medical center for company staff. Implementation of a mobile workshop to optimize resources and speed up the process of vehicle maintenance. Creation of technological networks to manage customers and their satisfaction. According to the market research carried out, average satisfaction was 8.5 out of 10. Considering the company to be serious and responsible with its clients and products, and, above all, showing a high level of professionalism in its operations. The best logistics are based on strategic planning, performance evaluation markers, and organizational behavior variables with which distribution conditions will be strengthened. The financial cost of this improvement plan project is a Net Present Value of USD 12,262.44 and an Internal Rate of Return of 53% with leverage. Without leverage the Net Present Value is USD 171,015.93; the Internal Rate of Return is 32%; and the WACC is 9%, showing that this project would be both feasible and profitable.